Breakthrough curve investigation for analysing effectiveness of CO2 adsorption using K2CO3 in fixed bed column. Issue 2 (April 2020) - Elizabeth, L; Heriyanto, H; Immah, H; Aqshanrilyan, K
Abstract: Carbon dioxide contributed great amount of Green House Gas (GHG) emission. Solid adsorption is one of the way to ease or lower carbon dioxide emission. The objective of this study is investigating breakthrough curve of CO2 adsorption using K2 CO3 solid in fixed bed column. Adsorption experiment is used to analysed adsorption capacity, breakpoint time and length of effective bed height. K2 CO3 used as adsorbent and rice husk as support. The K2 CO3 adsorption occurred under mild condition. The CO2 inlet and outlet concentration were analysed by acid-base titration. The highest adsorption capacity by K2 CO3 /rice husk is 0.2 mmol/g adsorbent at CO2 inlet flow rate 28 LPM (litre per minutes) by 50 gr K2 CO3 adsorbent. it is necessary to vary other parameter because CO2 flow rate (15, 9 and 28 LPM) and adsorbent amount (50-125 gr) do not affect adsorption capacity significantly.